PENGARUH PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Primadayani, Syurti (Jurnal Daya Saing, 2024)
This research aimed to find out the effect of the profitability and liquidity towards capital structure with company size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange. The method used is multiple linear analysis. The results obtained are partial profitability that does not significantly influence the capital structure, while liquidity has a significant effect on the capital structure. The results of the moderation research found that profitability and liquidity which are moderated by the variable company size only weakens the relationship between profitability and liquidity to the capital structure. Finally the author suggested to companies who are investing, so that before making an investment, investors should pay attention to the debt owned by the company. It was proved that liquidity gives significant influence towards capital structure, so that companies that have a good capital structure, it also has good liquidity, and the company deserves to be used as a place to invest Keywords: Profitability and liquidity